Incorporating oral health care education in undergraduate nursing curricula - a systematic review - Vandana Bhagat; Ha Hoang; Leonard A. Crocombe; Lynette R. Goldberg (BMC, 2020)
Abstract Background The recognised relationship between oral health and general health, the rapidly increasing older population worldwide, and changes in the type of oral health care older people require have raised concerns for policymakers and health professionals. Nurses play a leading role in holistic and interprofessional care that supports health and ageing. It is essential to understand their preparation for providing oral health care. Objective: To synthesise the evidence on nursing students' attitudes towards, and knowledge of, oral healthcare, with a view to determining whether oral health education should be incorporated in nursing education. Methods Data sources: Three electronic databases - PubMed, Scopus, and CINAHL. Study eligibility criteria, participants and interventions: Original studies addressing the research objective, written in English, published between 2008 and 2019, including students and educators in undergraduate nursing programs as participants, and conducted in Organisation of Economic Co-operation and Development countries. Study appraisal and synthesis methods: Data extracted from identified studies were thematically analysed, and quality assessment was done using the Mixed Methods Appraisal Tool. Results From a pool of 567 articles, 11 met the eligibility criteria. Findings documented five important themes: 1.) nursing students' limited oral health knowledge; 2.) their varying attitudes towards providing oral health care; 3.) the need for further oral health education in nursing curricula; 4.) available learning resources to promote oral health; and 5.) the value of an interprofessional education approach to promote oral health care in nursing programs. Limitations: The identified studies recruited small samples, used self-report questionnaires and were conducted primarily in the United States. Conclusions The adoption of an interprofessional education approach with a focus on providing effective oral health care, particularly for older people, needs to be integrated into regular nursing education, and practice. This may increase the interest and skills of nursing students in providing oral health care. However, more rigorous studies are required to confirm this. Nursing graduates skilled in providing oral health care and interprofessional practice have the potential to improve the oral and general health of older people.